Effects of disks on gravitational lensing by spiral galaxies - Bartelmann, Matthias; Leyb, Avraham (The astrophysical journal, 1998)
Gravitational lensing of a quasar by a spiral galaxy should often be accompanied by damped Lyα absorption and dust extinction due to the intervening gaseous disk. In nearly edge-on configurations, the surface mass density of the gas and stars in the disk could by itself split the quasar image and contribute significantly to the overall lensing cross section. We calculate the lensing probability of a disk-plus-halo mass model for spiral galaxies, including the cosmic evolution of the lens parameters. A considerable fraction of the lens systems produce two images with subarcsecond separation, straddling a nearly edge-on disk. Because of that, extinction by dust together with observational selection effects (involving a minimum separation and a maximum flux ratio for the lensed images) suppress the detection efficiency of spiral lenses in optical wave bands by at least an order of magnitude. The missing lenses could be recovered in radio surveys. In modifying the statistics of damped Lyα absorbers, the effect of extinction dominates over the magnification bias due to lensing.
Gesehen am 28.09.2017